2016
DOI: 10.1080/02640414.2016.1158851
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of anticipation by 3D motion capturing – a new method presented in karate kumite

Abstract: Anticipation is an important performance factor in karate kumite. A new approach analysing anticipation in realistic combat situations by motion capturing with a high temporal resolution is presented. The advantage of this approach is that both karate athletes interacting sports specific can be recorded synchronously; thus, the presented method has the potential to analyse visual information pickup due to coordination pattern of interaction between real athletes. The aim is to demonstrate the usability of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 20 publications
2
14
0
Order By: Relevance
“…The Mawashi geri is executed in high speed, being a very precise kick resulting in multiple points during fight 28 . One trait in this technique is the fact that it starts even before the opponent could detect the attack 29 . The Mawashi geri merits higher attention from coaches in their periodization programmes, being an efficient technique used by Karate athletes 19 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Mawashi geri is executed in high speed, being a very precise kick resulting in multiple points during fight 28 . One trait in this technique is the fact that it starts even before the opponent could detect the attack 29 . The Mawashi geri merits higher attention from coaches in their periodization programmes, being an efficient technique used by Karate athletes 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Two tactical behaviours in Kumite Karate, perception and anticipation, have not been thourougly investigated to date. Karate athletes must react to extreme and quick movements in a short period of time in order to neutralize incoming attakcs thus avoiding the opponent win 21 .…”
Section: Introductionmentioning
confidence: 99%
“…An equivalent movement used in Muay Thai is called,"switch stance" (Turner, 2009). In sports practice, these "early cues" (Petri et al, 2017) are also known as "Telegraphs" (TGs), describing movements or initiation actions prior to the actual technique start (e.g., leg elevation), which are sufficiently large to be detected and identified by the opponent. Wąsik (2011) reported that a "shifting the back-leg forward" TG starts about 400 ms before the kicking leg elevation, which is about 2/3 of the kicks' total duration (0.62 s).…”
Section: Introductionmentioning
confidence: 99%
“…Context information can be information about the position of the players in the field, the score, the knowledge about movement preferences (Loffing & Cañal-Bruland, 2017), or the interpersonal distance between athletes (e.g. Petri et al, 2016). Such context information are perceived all the time, while kinematic information become more important around ball contact or ball release (Runswick, Roca, Williams & McRobert, 2018).…”
Section: Introductionmentioning
confidence: 99%